Species diversity of cerambycid beetles at reclamation area of coal mining in Berau District, East Kalimantan, Indonesia - SUGIARTO SUGIARTO; CHANDRADEWANA BOER; DJUMALI MARDJI (Society for Indonesian Biodiversity, 2016)
Sugiarto, Boer C, Mardji D. 2016. Species diversity of cerambycid beetles at reclamation area of coal mining in Berau District, East Kalimantan, Indonesia. Biodiversitas 17: 200-207. Longhorn beetles (Cerambycidae) are amongst the most popular beetle families and hence lots of research has been carried out on the family. However, the presence of this beetle in the reclamation area of PT Berau Coal has not been investigated yet. PT Berau Coal is a coal company that has long been operated. In the former mining areas have been planted with reclamation plants. The study was carried out to determine the cerambycid beetle species diversity in three sites of the reclamation area, mainly Lati (L), Sambarata (S) and Binungan (B). This is the first report of cerambycid beetles diversity at areclamation area of PT Berau Coal. This study reveals a total of 16, 19 and 22 species with 100, 140 and 192 individuals respectively. Calculation with Simpson’s diversity index (1-D) resulted in highly index of biodiversity, namely 0.90, 0.89 and 0.89 respectively. These highly index of diversity is likely due to varied types of vegetation and distance from natural forest to study sites is relatively close. There were seven species respectively dominant at Lati and Sambarata reclamation areas, while at Binungan were six species.Simpson’s evenness index of Lati was the highest, followed by Sambarata and Binungan, that were 0.64, 0.53 and 0.41, respectively. This differences might be influenced by the ability of each beetle species to move to other habitats. Jaccard’s similarity indices at the three sites were relatively same; they were L with S = 0.45, L with B = 0.46 and S with B = 0.46. The similarity index reflects similar environmental conditions of the three study sites. From the viewpoint of nature conservation, it is concluded that post-mining areas canplay a key role in the conservation of beetle diversity since they are as new habitat for beetles species whose original habitats are now in critical condition due to human impact. An important task for future management of post-mining areas is to maintain successional processes and to prevent loss of habitat diversity through revegetation.